Foreign-Born Adults' Participation in Educational Activities: Evidence From Europe. Issue 2 (3rd April 2019) - Boeren, Ellen
Abstract : This article demonstrates that foreign-born adults in Europe tend to participate less in adult education activities compared to native-born adults living in the same country. However, this is mainly explained through the job-related nature of nonformal education. Foreign-born adults tend to participate more in formal adult education than native-born adults in a range of countries. Based on analyses using data from the Organization for Economic Cooperation and Development Programme on the International Assessment of Adult Competencies (PIAAC), this article shows that participation rates in European countries are mainly determined by adults' educational attainment and having a job and that countries with overall high participation rates have higher participation rates among foreign-born adults as well. Exploring the participation in adult education of foreign-born adults in European countries is important, as it is known that those adults perceive difficulties in finding a job and having their foreign credentials recognized in the new country context. Participation in adult education courses might help them in learning new or maintaining their already existing skills.